أثر وسائل التواصل الاجتماعي في حماية الهوية الثقافية الجزائرية - - بزي أسامة (جامعة محمد بوضياف بالمسيلة, 2025)
تتناول هذه الدراسة أثر مواقع التواصل الاجتماعي على الهوية الثقافية الجزائرية من خلال تحليل محتوى عدد من المؤثرين الرقميين، أبرزهم خبيب حفصة ومحمد دومير. في ظل التحولات الرقمية المتسارعة، أصبحت هذه المنصات فضاءً مركزيًا لإعادة تشكيل الرموز الثقافية، وهو ما يجعلها ذات تأثير مباشر على وعي الأفراد، خاصة فئة الشباب. وقد هدفت الدراسة إلى فهم طبيعة هذا التأثير، وتقييم مدى مساهمة المحتوى الرقمي في تعزيز أو تهديد الهوية الثقافية المحلية. بالاعتماد على المنهج الوصفي التحليلي، تم تحليل مضامين مختارة للمؤثرين، لتبيان حضور الرموز اللغوية، الدينية، والتاريخية. أظهرت النتائج أن مواقع التواصل الاجتماعي تُعد أداة مزدوجة التأثير، إذ يمكن أن تسهم في نشر التراث الثقافي أو تساهم في تهميشه، حسب مضمون الرسائل المقدمة ووعي صُنّاع المحتوى بأهمية الهوية الوطنية. Study Abstract: This study explores the impact of social media on Algerian cultural identity by analyzing the content of several digital influencers, notably Khouibib Hafsa and Mohamed Doumir. Amid rapid digital transformations, these platforms have become central spaces for reshaping cultural symbols, giving them a direct influence on individual awareness, especially among youth. The study aims to understand the nature of this influence and assess how digital content contributes to either reinforcing or threatening local cultural identity. Using a descriptive-analytical method, selected influencer content was analyzed to identify the presence of linguistic, religious, and historical symbols. The findings reveal that social media is a double-edged tool: it can help promote cultural heritage or contribute to its marginalization, depending on the content’s message and the level of awareness among content creators regarding the importance of national identity.